PENGARUH SISTEM AKUNTANSI MANAJEMEN, DESENTRALISASI, DAN TEKNOLOGI INFORMASI TERHADAP MENINGKATKAN KINERJA DAN EFISIENSI PERUSAHAAN - Saragih, Enzel Hikma Sari; Dela Mariana Nopela Br. Raja Gukguk; Elsa Arnelita Lubis; Eflin Kartika Sinaga (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to analyze the influence of management accounting systems, decentralization, and information technology on improving company performance and efficiency. Through a literature review approach, it was found that the integration of these three elements can strengthen strategic decision-making and operational efficiency. Management accounting systems provide relevant information for planning, control, and performance evaluation. Decentralization supports faster and more flexible decision-making, while information technology enhances speed and accuracy in data processing and financial reporting. However, Micro, Small, and Medium Enterprises (MSMEs) still face various challenges in implementing these systems, such as limited understanding of costing methods and minimal utilization of technology. This study offers recommendations for companies and MSMEs to strengthen their management accounting systems to enhance competitiveness in the era of digital economic transformation.